2018
DOI: 10.1016/j.jdsr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Candida is a protractive factor of chronic oral ulcers among usual outpatients

Abstract: SummaryAlthough many oral ulcers have similar clinical appearances, their etiologies can range from reactive to neoplastic to oral manifestations of dermatological diseases. In patients with an HIV infection, fungal diseases may cause ulceration in the oral cavity; however, there have been few studies of oral ulcerative lesions associated with Candida in patients without an HIV infection. Nevertheless, we encountered chronic oral ulcer associated with Candida among our frequent outpatients without an HIV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…primary immunodeficiencies, HIV, secondary immunodeficiencies caused by medications). Candida infection is unlikely to cause oral ulcerations, however acute pseudomembranous candidiasis or acute atrophic candidiasis may do so [ 21 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…primary immunodeficiencies, HIV, secondary immunodeficiencies caused by medications). Candida infection is unlikely to cause oral ulcerations, however acute pseudomembranous candidiasis or acute atrophic candidiasis may do so [ 21 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Ulcerative lesions are encountered in laryngeal disease, but although many ulcers have similar clinical appearances, their etiologies can vary from reactive to neoplastic. Although many studies have reported that fungal disease can cause oral ulcers, there have been few reports of oral ulcers associated with Candida, 17 while instead no manuscript of laryngeal ulcers associated with Candida secondary to steroid intake has been published before our documentation. The underlying mechanism of drug-induced ulceration is often unclear, and histopathological examination usually reveals nonspecific ulcer formation with marked infiltration as inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…is found as part of oral microbiota and can cause lesions as an opportunistic agent in immunosuppressed patients. It must be kept in mind at the time of a differential diagnosis of oral ulcers of unknown origin ( 7 ). We did not observed hyphae in biopsy or culture samples.…”
Section: Discussionmentioning
confidence: 99%